A Study on the Factors Influencing ChatGPT Users' Attitude: Drawing upon the Technology Acceptance Model Theory - Shi, Yiyi (International Journal of Computer Science and Information Technology, 2024)
The seeded of ChatGPT, OpenAI's latest innovation in 2022, has captured the public's attention due to the inactivated advancements in AI technology. This research, utilizing the Technology Acceptance Model (TAM), seeks to explore the impact of digital literacy on the perception of usefulness (PU), ease of use (PEOU), and the intention to use (IU). The results indicate that the perception of IU is positively influenced by both PU and PEOU. This research indicates that the enhancement of digital literacy among university students plays a significant role in shaping their PU and PEOU, subsequently leading to an increased intention to utilize this tool.